2020
DOI: 10.1002/anie.202006561
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization‐Driven Asymmetric Helical Assembly of Conjugated Block Copolymers and the Aggregation Induced White‐light Emission and Circularly Polarized Luminescence

Abstract: Controlling the self‐assembly morphology of π‐conjugated block copolymer is of great interesting. Herein, amphiphilic poly(3‐hexylthiophene)‐block‐poly(phenyl isocyanide)s (P3HT‐b‐PPI) copolymers composed of π‐conjugated P3HT and optically active helical PPI segments were readily prepared. Taking advantage of the crystallizable nature of P3HT and the chirality of the helical PPI segment, crystallization‐driven asymmetric self‐assembly (CDASA) of the block copolymers lead to the formation of single‐handed helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 75 publications
2
136
0
Order By: Relevance
“…However, subsequent extensions to other crystallizable polymer systems has led to major expansion of the field and has enhanced the possibility for a wide variety of applications. Studies reported since 2011 have involved PLLA, [165][166][167] PE, 168 PFDES, 38 and also hyperbranched poly(ether amine) capped with polyhedral oligomeric silsesquioxane, 143 PCL, 169,170 polycarbonate, 62,171 and π-conjugated polymers such polythiophene, [172][173][174][175] poly(3heptylselenophene), 176 PDHF, 177 oligo(p-phenylenevinylene) (OPV), 178,179 poly(cyclopentenylenevinylene) 180 and oligo(p-phenylene-ethynylene). 181 The use of the living CDSA seeded-growth approach to fabricate well-defined biopolymerbased assemblies has also been reported.…”
Section: The Living Cdsa Seeded Growth Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subsequent extensions to other crystallizable polymer systems has led to major expansion of the field and has enhanced the possibility for a wide variety of applications. Studies reported since 2011 have involved PLLA, [165][166][167] PE, 168 PFDES, 38 and also hyperbranched poly(ether amine) capped with polyhedral oligomeric silsesquioxane, 143 PCL, 169,170 polycarbonate, 62,171 and π-conjugated polymers such polythiophene, [172][173][174][175] poly(3heptylselenophene), 176 PDHF, 177 oligo(p-phenylenevinylene) (OPV), 178,179 poly(cyclopentenylenevinylene) 180 and oligo(p-phenylene-ethynylene). 181 The use of the living CDSA seeded-growth approach to fabricate well-defined biopolymerbased assemblies has also been reported.…”
Section: The Living Cdsa Seeded Growth Methodsmentioning
confidence: 99%
“…Recently, single-handed helical nanofibers with controlled length and handedness have been fabricated through the living CDSA of amphiphilic BCPs composed of a crystallizable P3HT core-forming block and a corona-forming segment comprising optically active helical poly(phenyl isocyanide) segments. 172 It was found that during the self-assembly process the chirality of helical poly(phenyl isocyanide) was transferred to the nanofibers. Figure 10a), concentric 2D block comicelles 142,144,145 (see Figure 10c) and hierarchical assembles 148,164 (see…”
Section: Optoelectronicsmentioning
confidence: 99%
“…CPL-active conjugated polymer assemblies have drawn great attention owing to their well-defined structure modification, tunable luminescent properties, and easy processing 63 , 64 . They can be constructed through the following two approaches: (1) self-assembly of chiral conjugated polymers, including main-chain chiral conjugated polymers and conjugated polymers with chiral side-chain; (2) doping achiral conjugated polymers with chiral additives.…”
Section: Cpl-active Organic Materials With Micro-/nano-structuresmentioning
confidence: 99%
“…Decorating the conjugated polymer with chiral pendants provides an alternative choice, and various CPL-active conjugated polymer systems ( 34–39 ) have been developed 64 , 68 70 , where the chiral pendants play an important role in the arrangement of the polymer chains. Typically, chiral π-conjugated block copolymers 34 composed of poly(3-hexylthiophene-2,5-diyl) (P3HT) and poly(phenyl isocyanide) (PPI) with chiral substituent were prepared 64 . Employing the crystallinity of P3HT and the chirality of PPI, the approach of crystallization-driven asymmetric self-assembly was developed to construct helical structures.…”
Section: Cpl-active Organic Materials With Micro-/nano-structuresmentioning
confidence: 99%
“…Among the developed helical polymers, polyisocyanide is of great interesting, because of its unique rod‐like helical structure and wide applications [36–42] . Polyisocyanide is generally prepared via the polymerization of the corresponding isocyanide monomer by using transition metal complexes or cations as catalysts [43–46] .…”
Section: Introductionmentioning
confidence: 99%